A randomized controlled trial testing a hyaluronic acid spacer injection for skin toxicity reduction of brachytherapy accelerated partial breast irradiation (APBI): a study protocol - Gerson M. Struik; Jeremy Godart; Gerda M. Verduijn; Inger-Karine Kolkman-Deurloo; Kim C. de Vries; Raymond de Boer; Linetta B. Koppert; Erwin Birnie; Ali Ghandi; Taco M. Klem; Jean-Philippe Pignol (Trials, 2018)
Abstract Background Accelerated partial breast irradiation (APBI) is a treatment option for selected early stage breast cancer patients. Some APBI techniques lead to skin toxicity with the skin dose as main risk factor. We hypothesize that a spacer injected between the skin and target volume reduces the skin dose and subsequent toxicity in permanent breast seed implant (PBSI) patients. Methods In this parallel-group, single-center, randomized controlled trial, the effect of a subcutaneous spacer injection on skin toxicity among patients treated with PBSI is tested. Eligibility for participation is derived from international guidelines for suitable patients for partial breast radiotherapy, e.g. women aged ≥ 50 years with a histologically proven non-lobular breast carcinoma and/or ductal carcinoma in situ (DCIS), tumor size ≤ 3 cm, node-negative, and PBSI technically feasible. Among exclusion criteria are neoadjuvant chemotherapy, lymphovascular invasion, and allergy for hyaluronic acid. For the patients allocated to receive spacer, after the PBSI procedure, 4–10 cc of biodegradable hyaluronic acid (Barrigel™, Palette Life Sciences, Santa Barbara, CA, USA or Restylane SubQ®, Galderma Benelux, Breda, the Netherlands) is injected directly under the skin using ultrasound guidance to create an extra 0.5–1 cm space between the treatment volume and the skin. The primary outcome is the rate of telangiectasia at two years, blindly assessed using Bentzen’s 4-point scale. Secondary outcomes include: local recurrence; disease-free and overall survival rates; adverse events (pain, redness, skin/subcutaneous induration, radiation dermatitis, pigmentation, surgical site infection); skin dose; cosmetic and functional results; and health-related quality of life. A Fisher’s exact test will be used to test differences between groups on the primary outcome. Previous studies found 22.4% telangiectasia at two years. We expect the use of a spacer could reduce the occurrence of telangiectasia to 7.7%. A sample size of 230 patients will allow for a 10% lost to follow-up rate. Discussion In this study, the effect of a subcutaneous spacer injection on the skin dose, late skin toxicity, and cosmetic outcome is tested in patients treated with PBSI in the setting of breast-conserving therapy. Our results will be relevant for most forms of breast brachytherapy as well as robotic radiosurgery, as skin spacers could protect the skin with these other techniques. Trial registration Netherlands Trial Register, NTR6549. Registered on 27 June 2017.